2019
DOI: 10.1186/s13293-019-0241-y
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the expression of cell adhesion molecules on microvesicles derived from cultured human brain microvascular endothelial cells treated with inflammatory and thrombotic stimuli

Abstract: Background There are sex differences in risk for stroke and small vessel ischemic disease in the brain. Microvesicles (MV) derived from activated cells vary by cell of origin and the stimulus initiating their release. MV released from cells activated by inflammatory and thrombotic factors have the potential to disrupt endothelial cells of the brain microvasculature. Therefore, experiments were designed to identify sex differences in the phenotype of MV released from cultured human brain microvascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…There are numerous studies which emphasize the difference of inflammatory response in males and females for various diseases and conditions [22][23][24], which would explain these results. In fact, it was demonstrated that females tend to have a higher number of leukocytes (more macrophages and more T and B lymphocytes) compared to males, more than double, this difference being explained by various values of tissue chemokines; also, resident leukocytes have a different phenotype in males and females [25].…”
Section: Resultsmentioning
confidence: 99%
“…There are numerous studies which emphasize the difference of inflammatory response in males and females for various diseases and conditions [22][23][24], which would explain these results. In fact, it was demonstrated that females tend to have a higher number of leukocytes (more macrophages and more T and B lymphocytes) compared to males, more than double, this difference being explained by various values of tissue chemokines; also, resident leukocytes have a different phenotype in males and females [25].…”
Section: Resultsmentioning
confidence: 99%
“…EXs and EMVs: (i) are released under normal physiological conditions, but are also discharged from parent cells upon cellular activation, hypoxia and/or hyperoxia, senescence, apoptosis and disease via a paracrine- and endocrine-type type action to their target cells; (ii) represent one of the major biological mechanisms for genetic exchange, immune signaling and the spread of inflammation and disease between cells of the host; (iii) EX and EMV trafficking in the mammalian CNS is a particularly robust, active and dynamic process (Valadi et al, 2007 [ 26 ]; Hunter et al, 2008 [ 36 ]; Deng et al, 2018 [ 34 ]; Stahl et al, 2019 [ 9 ]; Arbo et al, 2020 [ 6 ]; Hou et al, 2020 [ 37 ]). The human brain and retina, CNS, cerebrospinal fluid (CSF), neurovasculature, as well as the systemic circulation, are particularly rich sources of EXs, MPs and EMVs, suggesting that they are significant components of a highly active multi-component extracellular signaling and communication system (Trotta et al, 2018 [ 38 ]; Seyedrazizadeh et al, 2020 [ 39 ]; Song et al, 2020 [ 40 ]).…”
Section: Microvesicle Signaling In Neurodegenerationmentioning
confidence: 99%
“…The discovery of the important role of miRNAs in the regulation of the transcriptome of a cell was made about ~15 years ago and was shortly followed by the first reports of altered miRNA abundance, speciation and complexity in the limbic system of Alzheimer’s disease (AD) brains (Lukiw 2007 [ 60 ]) This included a significant up-regulation of what are now known as “ pro-inflammatory miRNAs ”, including miRNA-34a, miRNA-125b, miRNA-146a, miRNA-155 and others in the parenchyma of the temporal lobe neocortex (Lukiw 2007 [ 60 ]; Valadi et al, 2007 [ 26 ]; Hunter et al, 2008 [ 36 ]; Sethi and Lukiw 2009 [ 22 ]; Zhao et al, 2015 [ 61 ]; Hammond 2016 [ 28 ]). The first reports of EXs and EMVs being loaded with ribonucleic acid cargoes, such as specific miRNAs and mRNAs, first came about ~12 years ago: (i) from the microarray analysis of mast cells involved in innate and adaptive immunity, autoimmunity, and inflammation (Valadi et al, 2007 [ 26 ]); (ii) from studies of specific miRNAs, mRNAs and angiogenic proteins in glioblastoma and neuroblastoma tumor cells that have released EXs and EMVs (Skog et al, 2008 [ 25 ]; Columbo et al, 2014 [ 13 ]; Briand et al, 2020 [ 8 ]).…”
Section: Selective Micrornas In Exs and Emvsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inducible markers used to identify endothelial dysfunction or injury are similar between the human and murine endothelium, with few exceptions. CD62E (E‐selectin) and CD106 (V‐CAM) are human‐specific markers of endothelial damage not used in murine panels [5,18,20,28‐39]. A full list of inducible markers for human endothelial cells can be found in Table 3.…”
Section: Inducible Markersmentioning
confidence: 99%